Microsurgical Breast Reconstruction: Maximizing Success - Buntic, Rudolf; Li, Alexander Y. (Seminars in Plastic Surgery, 2022)
Breast reconstruction is becoming increasingly recognized as a fundamental component in comprehensive breast cancer treatment. The primary goal for any reconstruction is to safely restore a natural appearing breast. When it comes to achieving the elements of size, shape, symmetry, and softness, the use of autologous tissue has many advantages. The approach to autologous breast reconstruction has changed substantially over the years as microsurgical free tissue transplants become more routine and accessible. While a variety of flap donor sites exist, careful flap selection based on surgical history and the availability of donor tissue is critical in achieving reliable results. This article reviews the clinical considerations in patient evaluation, donor site selection, and surgical approach taken at the Buncke Clinic.
Keywords: breast reconstruction; autologous breast reconstruction; DIEP; TUG; PAP; SGAP